Networks of value added trade - Jo\~ao Amador; Sónia Cabral (European Central Bank (ECB), 2016)
Global Value Chains (GVCs) became the paradigm for the production of most goods and services around the world. Hence, interconnections among countries can no longer be adequately assessed through standard bilateral gross trade flows and new methods of analysis are needed. In this paper, we compute measures of network analysis and apply visualisation tools to value added trade flows in order to understand the nature and dynamics of GVCs. The paper uses data on the bilateral foreign value added in exports for the period 1995-2011 and, in each year, GVCs are represented as directed networks of nodes (countries) and edges (value added flows). The analysis is extended beyond total trade flows to discuss the distinct roles of goods and services in GVCs. Moreover, the differences between Germany, the US, China and Russia as major suppliers of value added in GVCs are also examined.
Keywords: F12; F14; C67; 330; global value chains; input-output tables; international trade; network analysis